What Motivates Nonprofit Organizations' Top Managers to Volunteer? - TAYŞİR, EYÜP AYGÜN (My University, 2013)
In this empirical study we analyzed 119 executives from Turkish nonprofit organizations with the aim of providing evidence to answer the question of what motivates governance volunteers to volunteer. Moreover, we tested whether organizational mission, managerial position, and age cause a difference among governance volunteers' volunteer motivation. Factor analysis revealed that there were five factors underlying the volunteer motivation concept, and although a combination of altruistic and egoistic needs leads individuals to volunteer, the primary reason was altruistic. Contrary to our assumptions, we found out that there was no difference between the determinants of volunteer motivation of governance volunteers from different managerial positions or from organizations with different missions. However, we found that determinants of volunteer motivation differ depending on age. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: governance volunteers; nonprofit organizations; volunteer motivation